The lncRNA H19 promotes epithelial to mesenchymal transition by functioning as miRNA sponges in colorectal cancer - Liang, Wei-Cheng; Fu, Wei-Ming; Wong, Cheuk-Wa; Wang, Yan; Wang, Wei-Mao; Hu, Guo-Xin; Zhang, Li; Xiao, Li-Jia; Wan, David Chi-Cheong; Zhang, Jin-Fang; Waye, Mary Miu-Yee (Oncotarget, 2015)
Recently, the long non-coding RNA (lncRNA) H19 has been identified as an oncogenic gene in multiple cancer types and elevated expression of H19 was tightly linked to tumorigenesis and cancer progression. However, the molecular basis for this observation has not been characterized in colorectal cancer (CRC) especially during epithelial to mesenchymal transition (EMT) progression. In our studies, H19 was characterized as a novel regulator of EMT in CRC. We found that H19 was highly expressed in mesenchymal-like cancer cells and primary CRC tissues. Stable expression of H19 significantly promotes EMT progression and accelerates in vivo and in vitro tumor growth. Furthermore, by using bioinformatics study and RNA immunoprecipitation combined with luciferase reporter assays, we demonstrated that H19 functioned as a competing endogenous RNA (ceRNA) for miR-138 and miR-200a, antagonized their functions and led to the de-repression of their endogenous targets Vimentin, ZEB1, and ZEB2, all of which were core marker genes for mesenchymal cells. Taken together, these observations imply that the lncRNA H19 modulated the expression of multiple genes involved in EMT by acting as a competing endogenous RNA, which may build up the missing link between the regulatory miRNA network and EMT progression.